Private Power / Multinational Coroporations for the Survival of Our Planet - Madsen Axel (Allyn And Bacon, 1980)
This book shows what is going right in today's and tomorrow's world. Introduction, Power Beyond Flag and Country, By Any Other Name, Who are They?, The Next Ten, Geo Banking, Now and About Our Little Bill, How Do They Do It?, End of Innocence, Energy Biz, The Enterprising State, Ali Baba, Stuck in Neutral, Mutations, The UN's Learning Towers, North-South, The Long March, Future Tech, Selected Readings, Index.